Intra‐procedural and delayed bleeding after resection of large colorectal lesions: The SCALP study. Issue 10 (1st December 2019) - Amato, Arnaldo; Radaelli, Franco; Correale, Loredana; Di Giulio, Emilio; Buda, Andrea; Cennamo, Vincenzo; Fuccio, Lorenzo; Devani, Massimo; Tarantino, Ottaviano; Fiori, Giancarla; De Nucci, Germana; De Bellis, Mario; et al.
Abstract : Background and aim: The safety of endoscopic resection of large colorectal lesions (LCLs) (≥20 mm) is clinically relevant. The aim of the present study was to assess the rate of post‐resection adverse events (AEs) in a real‐life setting. Patients and methods: In a prospective, multicentre, observational study, data from consecutive resections of LCLs over a 6‐month period were collected in 24 centres. Patients were followed up at 15 days from resection for AEs. The primary endpoint was intra‐procedural bleeding according to lesion morphology. Secondary endpoints were delayed bleeding and perforation. Patient and polyp characteristics, and polypectomy techniques were analysed with respect to the bleeding events. Results: In total, 1504 patients (female/male: 633/871, mean age, 66.1) with 1648 LCLs (29.1% pedunculated and 70.9% non‐pedunculated lesions) were included. Overall, 168 (11.2%) patients had post‐resection bleeding (8.5 and 2.0% immediate and delayed, respectively), while 15 (1.0%) cases of perforation occurred. Independent predictors of immediate bleeding for pedunculated lesions were bleeding prophylaxis (odds ratio (OR) 0.28, 95% confidence interval (CI) 0.13–0.62), simple polypectomy (versus endoscopic mucosal resection, OR 0.38, 95% CI 0.17–0.88) and inpatient setting (OR 2.21, 95% CI 1.07–5.08), while bleeding prophylaxis (OR 0.37, 95% CI 0.30–0.98), academic setting (OR 0.27, 95% CI 0.12–0.54) and size (OR 1.03, 95% CI 1.00–1.05) were predictors for those non‐pedunculated. Indication for colonoscopy (screening versus diagnostic (OR 0.33, 95% CI 0.12–0.86)), antithrombotic therapy (OR 3.12, 95% CI 1.54–6.39) and size (OR 2.34, 95% CI 1.12–4.87) independently predicted delayed bleeding. Conclusions: A low rate of post‐resection AEs was observed in a real‐life setting, reassuring as to the safety of endoscopic resection of ≥2 cm colorectal lesions. Bleeding prophylaxis reduced the intra‐procedural bleeding risk, while antithrombotic therapy increased delayed bleeding. CLINICALTRIAL: (NCT02694120).